2018
DOI: 10.15406/mojwh.2018.07.00161
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity: A Brief Challenge on Prevalence, Complications and Physical Activity among Men and Women

Abstract: Obesity is a major problem for public health due to weight gain from imbalance between energy intake and energy expenditure. According to published data by World Health Organization (WHO), obesity was increased rapidly from outset of last decades of 1900. Prevalence of obesity is accepted as a socioeconomic challenge in present decade. Based on this topic, in particular since 1980 decade, if this trend cannot be reversed or at least restrained, high levels of obesity will naturally lead to increases in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Hence, the BMI is an easy and noninvasive way to evaluate the degree of excess weight in adults 2 . As per epidemiological reports, the proportion of overweight and obese adults increased globally from 28.8 per cent in 1980 to 36.9 per cent in 2013 for men and from 29.8 per cent to 38 per cent for women 1 . Thus, prevalence of high BMI rapidly increased in last decades.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Hence, the BMI is an easy and noninvasive way to evaluate the degree of excess weight in adults 2 . As per epidemiological reports, the proportion of overweight and obese adults increased globally from 28.8 per cent in 1980 to 36.9 per cent in 2013 for men and from 29.8 per cent to 38 per cent for women 1 . Thus, prevalence of high BMI rapidly increased in last decades.…”
Section: Introductionmentioning
confidence: 78%
“…BMI is a numerical figure that gives an idea of the physical type of the human body and its subgroups are often categorised qualitatively. A BMI of less than 18.5 is classified as underweight, from 18.5 to 25 as normal, between 25 and 30 as overweight and more than 30 is termed as obesity 1 . Hence, the BMI is an easy and noninvasive way to evaluate the degree of excess weight in adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Increased body weight is associated with adverse effects on the physiological body functions and thus, is implicated in various chronic disorders such as osteoarthritis, cardiovascular diseases, type 2 DM, respiratory disease, cancers, and premature mortality. 1,2,[14][15][16] As compared to office BP monitoring, ABPM is better predictor of hypertension-mediated organ damage (HMOD). 17 Moreover, closer relationship has been demonstrated between 24 h mean ambulatory BP and morbid or fatal events, and it is more sensitive risk predictor of CV outcomes than office BP.…”
Section: Systolic Ambulatory Bp Patternmentioning
confidence: 99%
“…In recent years, overweight and obesity in childhood and adolescence have become an important health problem all over the world, especially in developed countires due to the decrease in physical activity [1]. The World Health Organization (WHO) stated that approximately 40% of individuals over the age of 18 were overweight [2], and studies have shown that the rate of overweight and obesity is more common in women than in men [3]. In Turkey, as in similar studies carried out worldwide prevalence, rate of overweight and obesity was higher in women compared to men [4].…”
Section: Introductionmentioning
confidence: 99%